2014
DOI: 10.1021/tx500216a
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Biological Activities of Carboxyethylpyrrole Ethanolamine Phospholipids (CEP-EPs)

Abstract: Oxidation of docosahexaenoate phospholipids produces 4-hydroxy-7-oxo-hept-5-eonyl phospholipids (HOHA-PLs) that react with protein lysyl ε-amino residues to generate 2-ω-carboxyethylpyrrole (CEP) derivatives, endogenous factors that induce angiogenesis in the retina and tumors. It seemed likely, but remained unproven, that HOHA-PLs react with ethanolamine phospholipids (EPs) in vivo to generate CEP-EPs. We now show that CEP-EPs are present in human blood at 4.6-fold higher levels in age-related macular degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 28 publications
1
59
0
Order By: Relevance
“…Although the biological activities and role of such derivatives in vivo have been widely studied for the past 3 decades, 7,8 studies of similar derivatives of phosphatidylethanolamine are very limited to date. 6,11 Evidence supports the notion that a variety of PE adducts and derivatives may form during conditions of oxidative stress in vivo. 9,11,32 Moreover, recent in vitro studies have shown that PE is the preferred target for modification by some lipid aldehydes.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Although the biological activities and role of such derivatives in vivo have been widely studied for the past 3 decades, 7,8 studies of similar derivatives of phosphatidylethanolamine are very limited to date. 6,11 Evidence supports the notion that a variety of PE adducts and derivatives may form during conditions of oxidative stress in vivo. 9,11,32 Moreover, recent in vitro studies have shown that PE is the preferred target for modification by some lipid aldehydes.…”
Section: Discussionmentioning
confidence: 67%
“…6,11 Evidence supports the notion that a variety of PE adducts and derivatives may form during conditions of oxidative stress in vivo. 9,11,32 Moreover, recent in vitro studies have shown that PE is the preferred target for modification by some lipid aldehydes. 10 However, the biological activities of such adducts and/or derivatives have just recently attracted attention and cellular receptors recognizing them are not known.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…5G). Furthermore, C22:6 LPE and related metabolites can be oxidized to form 2-ω-carboxyethyl pyrrole (CEP) protein derivatives (34), whose levels were higher in the photoreceptor cell inner and outer segments and RPE of HG than in LG and HGxoLG mice (Fig. 4 I and J).…”
Section: Resultsmentioning
confidence: 99%